Pengaruh Keaktifan Mahasiswa Berorganisasi dan Prestasi Belajar terhadap Kesiapan Kerja Mahasiswa S1 Pendidikan Ekonomi Universitas PGRI Wiranegara - Ridwan, Muhammad; Pradikto, Sugeng (Journal of Science and Education Research, 2025)
This study examines how active students in organizations and academic achievement affect the work readiness of undergraduate students in Economics Education at Universitas PGRI Wiranegara. Using a quantitative approach and survey method on 23 students, data were collected through a questionnaire with a Likert scale, which was then analyzed using the multiple linear regression method. The validity test resulted in findings that all variables were valid, with an average rrr count for Organizational Activity (X1) = 0.677, Learning Achievement (X2) = 0.702, and Work Readiness (Y) = 0.736, greater than the r table of 0.4132. The regression results showed that the analysis results showed that activeness in the organization had no effect on work readiness (Sig = 0.807), while learning achievement had a significant positive effect (Sig = 0.000). Simultaneously, both variables contributed 63.2% to work readiness, with the rest influenced by other factors. This study recommends that universities create programs that balance academic and non-academic development in order to produce competent graduates.